2013
DOI: 10.1002/hep.26428
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of naturally occurring transmissible chronic hepatitis B virus infection among Macaca fascicularis from mauritius island

Abstract: Despite a high prevalence of hepatitis B virus (HBV) infection in endangered apes, no HBV infection has been reported in small, old-world monkeys. In search for a small, nonhuman primate model, we investigated the prevalence of HBV infection in 260 macaque (Cercopithecidae) sera of various geographical origins (i.e., Morocco, Mauritius Island, and Asia). HBV-positive markers were detected in cynomolgus macaques (Macaca fascicularis) from Mauritius Island only, and, remarkably, HBV DNA was positive in 25.8% (31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 49 publications
(58 reference statements)
1
66
4
1
Order By: Relevance
“…This is supported by the finding that geographical regions with potentially high HBV transmission rates between human and nonhuman primates are also areas of high HBV prevalence among humans (i.e., Southeast Asia and Africa). There are several reports of known cross-species transmission cases, such as human HBV identified from chimpanzees (Hu et al 2000;Takahashi et al 2000), the identification of human/primate HBV recombinants (Magiorkinis et al 2005;Simmonds and Midgley 2005), infection of Mauritian macaques with human HBV (Dupinay et al 2013), and a gibbon variant isolated from a chimpanzee (Grethe et al 2000), which would lend substantial credence to this model.…”
Section: Theories Of Hbv Originsmentioning
confidence: 93%
“…This is supported by the finding that geographical regions with potentially high HBV transmission rates between human and nonhuman primates are also areas of high HBV prevalence among humans (i.e., Southeast Asia and Africa). There are several reports of known cross-species transmission cases, such as human HBV identified from chimpanzees (Hu et al 2000;Takahashi et al 2000), the identification of human/primate HBV recombinants (Magiorkinis et al 2005;Simmonds and Midgley 2005), infection of Mauritian macaques with human HBV (Dupinay et al 2013), and a gibbon variant isolated from a chimpanzee (Grethe et al 2000), which would lend substantial credence to this model.…”
Section: Theories Of Hbv Originsmentioning
confidence: 93%
“…Reports that HBV could also be transmitted to, and serially passaged in, rhesus monkeys could not be confirmed (London et al 1972). Similarly, a more recent report showed HBV replication in a Barbary macaque (Macaca sylvanus) after transfection of cloned HBV DNA, but serial passage and persistent infection in these animals was not observed (Gheit et al 2002;Dupinay et al 2013). In contrast, gibbons (genus Hylobates) at the International Center for Gibbon Studies (Santa Clarita, CA) were positive for markers of ongoing or past HBV infection and phylogenetic analysis of the isolated HBV sequences suggested that the gibbons, most likely, had been infected by transmission of HBV from humans (Lanford et al 2000).…”
Section: Establishing the Chimpanzee As An Hbv Model Systemmentioning
confidence: 97%
“…This observation is consistent with two previous studies, providing serological evidence of HBV infection in gibbons inoculated with human HBsAgpositive saliva or semen (Bancroft et al 1977;Scott et al 1980). Finally, it was shown that a Macaca fascicularis colony from Mauritius Island was naturally infected with a human HBV isolate (Dupinay et al 2013). Macaques might become an alternative model to chimpanzees for the study of therapeutic approaches against HBV infections (Bukh et al 2013).…”
Section: Establishing the Chimpanzee As An Hbv Model Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement of these models is now in progress with genetic engineering of mouse lineage to express hNTPC, as well as to engineer doubly humanized mice for both human hepatocytes and the human immune system. The development of more robust cell culture models and small primate models to recapitulate HBV infection and its pathogenesis is also highly desirable (Dupinay et al 2013;Shlomai et al 2014). …”
Section: Identification Of Novel Drug Targetsmentioning
confidence: 99%